2001
DOI: 10.1093/ije/30.3.580
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and association between herpes simplex virus types 1 and 2-specific antibodies in attendees at a sexually transmitted disease clinic

Abstract: Seroprevalence of HSV-1 and HSV-2 is falling among STD clinic attendees in Rotterdam. A changing pattern of risk factors for HSV-1 seropositivity indicates increasing sexual transmission of HSV-1. Seropositivity for HSV-2 correlated with known risk factors. A previous HSV-1 infection does not reduce susceptibility to subsequent genital HSV-2 infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
6
14
0
1
Order By: Relevance
“…Recently, HSV-1 seropositivity was associated with the female sex (9,31). This finding agrees with studies showingthat HSV-1-specific antibodies are generally more abundant in female mice than in male mice-a difference that disappears upon castration (22).…”
Section: Discussionsupporting
confidence: 86%
“…Recently, HSV-1 seropositivity was associated with the female sex (9,31). This finding agrees with studies showingthat HSV-1-specific antibodies are generally more abundant in female mice than in male mice-a difference that disappears upon castration (22).…”
Section: Discussionsupporting
confidence: 86%
“…High HSV-2 seroprevalences have been well documented among MSM groups in developed countries [4], with rates as high as 26%-66% in several US cities [5,6], 33%-58% in Amsterdam [7,8], 15% in Rotterdam [9], 51%-86% in Rome [10], and 11%-61% in London [11]. HSV-2 seroprevalence data from developing countries have been generated primarily from African and Asian countries [12] and have focused on non-MSM risk groups, such as female sex workers, bar workers, and STI clinic attendees [13].…”
mentioning
confidence: 99%
“…There are conflicting results from studies on the risk of HSV-1 positive patients of acquiring HSV-2 that are reported that previous HSV-1 infection does not reduce susceptibility to subsequent genital HSV-2. 28 Furthermore, our results indicate statistically significant a higher prevalence of HSV-2 IgG in HIV-positive patients when compared to 5% HIV-negative patients. This finding is consistent with most previous studies in other countries.…”
Section: Discussionmentioning
confidence: 48%